Development and Characterization of Calcium Lactate-Activated Sodium Alginate-Gum Arabic Edible Films - Mulyani, Sri; Dharmawan, Mohamad Rizky; Mesias, Inish Chris; Pratama, Yoga (Journal of Applied Food Technology, 2025)
Indonesia generated approximately 12.87 million tons of plastic waste in 2023, highlighting the urgent need to develop biodegradable alternatives such as edible films. This study investigated the effect of sodium alginate - gum arabic ratios on the physical and mechanical properties of edible films, combined with a calcium lactate spray activation technique aimed at enhancing film crosslinking, fasten gelling speed and improve performance. A completely randomized design with four treatments (1:1, 2:1, 3:1, and 4:1 ratios of sodium alginate and gum arabic) and five replications was applied. Parameters evaluated included thickness, water vapor transmission rate (WVTR), tensile strength, elongation, and microscopic morphology. Results showed that higher sodium alginate concentrations significantly increased film thickness (0.023– 0.094 mm) and significantly improved barrier properties, as indicated by lower WVTR values (69–94 g/m²/day). Tensile strength varied across treatments, reaching the highest value at the 1:1 ratio (8.24 MPa), while elongation peaked at the 2:1 ratio (30.94%), suggesting an optimal balance between flexibility and strength. Microscopic observation revealed fewer air bubbles and more homogeneous structures at higher sodium alginate levels. The introduction of calcium lactate spray activation, rather than conventional immersion or solution mixing, represents a novel crosslinking strategy that is suitable for edible film production. This method demonstrates a promising pathway toward the development of sustainable and high-performance biodegradable packaging materials.